Phylogeography of Petrolisthes armatus, an invasive species with low dispersal ability - Alexandra Hiller (Nature Portfolio, 2017)
Abstract Theoretically, species with high population structure are likely to expand their range, because marginal populations are free to adapt to local conditions; however, meta-analyses have found a negative relation between structure and invasiveness. The crab Petrolisthes armatus has a wide native range, which has expanded in the last three decades. We sequenced 1718 bp of mitochondrial DNA from native and recently established populations to determine the population structure of the former and the origin of the latter. There was phylogenetic separation between Atlantic and eastern Pacific populations, and between east and west Atlantic ones. Haplotypes on the coast of Florida and newly established populations in Georgia and South Carolina belong to a different clade from those from Yucatán to Brazil, though a few haplotypes are shared. In the Pacific, populations from Colombia and Ecuador are highly divergent from those from Panamá and the Sea of Cortez. In general, populations were separated hundreds to million years ago with little subsequent gene flow. High genetic diversity in the newly established populations shows that they were founded by many individuals. Range expansion appears to have been limited by low dispersal rather than lack of ability of marginal populations to adapt to extreme conditions.